"Dear Diary": A Preliminary Study of the Effects of Consistency Modification on Three Dimensions of Wellness. (November 2018) - Archer, Brent; Azios, Jamie; Azios, Michael; Becerril, Stefanie; Heels, Jane
Few studies of the ways in which consistency modification might affect dimensions of wellness exist. The aim of this study is to furnish preliminary findings on the effects that consistency modification has on a range of aspects of living. The authors (five speech-language pathologists [SLPs]) restricted our oral intake to thickened liquids and purees for 1 week. During this time, we kept diaries and chose to focus on three domains of wellness namely emotional, social, and intellectual well-being. The diaries we generated were subjected to thematic analysis. The thematic analysis we conducted revealed that dietary restrictions had a sizable effect on the outlined dimensions of wellness. By pursuing this line of research, and recording and analyzing the views of people with dysphagia, researchers can understand the broader costs of consistency modification. Furthermore, our findings suggest that some form of disability stimulation might enhance educational outcomes for student SLPs.